Malaria Aggravates Economic Hardships - Eldeepj, Tawfik (Gezira Journal of Health Sciences; Vol 1 No 1 (2004), 2004)
Introduction. The health care system in the Sudan is one of the oldest designs in Africa. What is impressive about the health system in the Sudan are the expansions of the health care infrastructure in the rural setting during the last decade. There had been an increase of over 100 in health centers, primary health care units and a number of lavout of rural hospitals